Uczestnictwo w sieci EURES jako zadanie publicznych służb zatrudnienia w Polsce - Gilga, Krystyna; Hasińska, Zofia; Sipurzyńska-Rudnicka, Katarzyna (Participation in the EURES network as a challenge for public rrecruitment services in Poland, 2006)
After Poland’s accession to the EU, public recruitment services became part of the European Recruitment Services - EURES. The article presents the process of preparing theses services to participate in the EURES network and evaluation of one year’s experience of international recruitment function operation, on the example of job departments in the Wroclaw agglomeration. In the evaluation, staffing problems of EURES assistants as well as providing suitable office rooms, good information flow between different levels of recruitment services, and ill matching of qualifications and preferences of job seekers to the offers submitted by foreign employers were taken into consideration.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (13); 2006; nr 1127, s. 178-191